Transformation of Natural Zeolites by the Fusion-Hydrothermal Method for Ammonium Adsorption - Lestariningsih, Devi; Kurniawan, Teguh; Nuryoto, Nuryoto (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2023)
Zeolite application as an ammonium adsorbent has been widely studied. However, there is no previous research on transformation of Malang natural zeolite and its application as ammonium adsorbent. In this study, characterization of the zeolite was carried out by XRD, XRF, nitrogen adsorption-desorption, SEM and FTIR tests. With the addition of 18 g of NaOH and heated with temperature of 550 0C for 2 h during the fusion, continued with aging for 18 h and temperature 100 0C during hydrothermal stage, the fusion-hydrothermal method had transformed Malang natural zeolite which dominated by quartz and small amount of mordenite into transformed zeolite dominated by zeolite X. Malang natural zeolite best fitted the Elovich adsorption kinetics model with  0.0096 and ẞ 11.93 and SSE 0.003 and Langmuir isotherm model with qmax 32.38 mg/g and KL 0.01 L/mg with SSE 0.27, while the transformed zeolite best fitted the Intraparticle diffusion model with ki 0.0084 and C 0.017 with SSE 0.006 and Freundlich isotherm model with KF 0.00035 L2.56/(mg1.56/g) and n 0.39 with SSE 1.17. Fusion-hydrothermal has changed the crystal shape from mostly the broken needle shape to round cube shapes, decreased the Si/Al ratio from 5.56 to 1.15, and increased the surface area from 43.5 m2/g to 89.8 m2/g.